Antistatic plastic packaging film and preparation method thereof
By introducing raw materials such as thiophene-3-ethanol and acryloyl chloride into the plastic packaging film, functionalized polyethylene and modified fillers are prepared to form a polythiophene structure, which solves the problem of static electricity and damage caused by plastic packaging film, and achieves efficient anti-static and mechanical properties improvement.
Patent Information
- Application Number
- CN202411116872.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-08-15
AI Technical Summary
At this stage, plastic packaging film is prone to static electricity, adsorbing dust, and is prone to damage during transportation.
Modified monomers were prepared by reacting thiophene-3-ethanol, acryloyl chloride, triethylamine and tetrahydrofuran, and reacted with methacryloyloxyethyltrimethylammonium chloride, 4-vinylaniline and azobisisobutyronitrile to form additives. Then react with maleic anhydride, toluene and p-methylbenzenesulfonic acid to prepare a modified additive and grafted with high-density polyethylene to form functionalized polyethylene. Then, under the action of ferric chloride, it reacts with the modified filler to form a polythiophene structure, and finally an anti-static plastic packaging film is produced through a twin-screw extruder and blow molding technology.
The prepared anti-static plastic packaging film has good conductivity and mechanical properties, which can effectively prevent static dust absorption, reduce the risk of damage during transportation and extend the service life.
Smart Images

Figure BDA0004993874990000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antistatic packaging film preparation, and in particular to an antistatic plastic packaging film and a preparation method thereof. Background Art
[0002] Packaging film has very important and extensive uses in modern production and life. Among them, plastic packaging film has the largest demand in the huge flexible packaging market. Plastic packaging film can be closely attached to the goods and is suitable for packaging of various shapes. It has beautiful appearance, hygiene, safety, transparency, sealing, fixation, dust and moisture resistance and other functions. At present, the commonly used plastic packaging film materials are mainly polyvinyl chloride, polyethylene, polypropylene and polystyrene. Polypropylene is widely used in automobiles, home appliances, packaging, medical and building materials due to its good heat resistance, chemical corrosion resistance, creep resistance, easy processing and low price. It has become the second largest plastic in the world. However, polypropylene is a typical insulating material, which is very easy to generate static electricity due to friction or contact, which brings great inconvenience to production safety and daily life. In severe cases, it may even cause fire and explosion, which greatly limits the scope of application of polypropylene. Summary of the invention
[0003] The purpose of the present invention is to provide an antistatic plastic packaging film and a preparation method thereof, which solves the problem that the current plastic packaging film is prone to generate static electricity to absorb dust and is prone to damage during transportation.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing an antistatic plastic packaging film specifically comprises the following steps:
[0006] Step A1: thiophene-3-ethanol, acryloyl chloride, triethylamine and tetrahydrofuran are mixed, and reacted for 10-15 hours at a speed of 120-150 r / min and a temperature of 45-50° C. to obtain a modified monomer; methacryloyloxyethyl trimethylammonium chloride, 4-vinylaniline, the modified monomer and DMF are uniformly mixed, and azobisisobutyronitrile is added at a speed of 200-300 r / min and a temperature of 75-80° C., and the mixture is stirred and reacted for 5-7 hours to obtain an additive;
[0007] Step A2: the additive, maleic anhydride, toluene and DMF are mixed, and the reaction is carried out for 1-1.5 hours at a speed of 120-150 r / min and a temperature of 20-25° C., and then p-toluenesulfonic acid is added, and the temperature is raised to 110-120° C. and the reaction is continued for 3-5 hours to obtain a modified additive, and the modified additive, high-density polyethylene, dibenzoyl peroxide and toluene are uniformly mixed, and the reaction is carried out for 4-6 hours at a temperature of 150-155° C. to obtain a functionalized polyethylene;
[0008] Step A3: Evenly mix the functionalized polyethylene, modified filler, thiophene and toluene, stir and add ferric chloride at a rotation speed of 60-80 r / min and a temperature of 100-110°C, react for 10-15 hours, remove the ferric chloride to obtain modified polyethylene, add the modified polyethylene into a twin-screw extruder, extrude and blow mold into a film at a temperature range of 160°C, 170°C, 170°C, 175°C, 185°C, 175°C and 170°C to obtain an antistatic plastic packaging film.
[0009] Furthermore, the molar ratio of thiophene-3-ethanol, acryloyl chloride and triethylamine in step A1 is 1:1:1.1, the molar ratio of methacryloyloxyethyltrimethylammonium chloride, 4-vinylaniline and the modified monomer is 4:1:2, and the amount of azobisisobutyronitrile is 0.3% of the total mass of methacryloyloxyethyltrimethylammonium chloride, 4-vinylaniline and the modified monomer.
[0010] Furthermore, the molar ratio of the amino group and maleic anhydride on the additive described in step A2 is 1:1.1, the amount of p-toluenesulfonic acid is 30% of the mass of the additive and maleic anhydride, the amount ratio of the modified additive, high-density polyethylene, dibenzoyl peroxide and toluene is 0.5g:5g:0.25g:40mL, and the high-density polyethylene model is M80064.
[0011] Furthermore, the mass ratio of the functionalized polyethylene, modified filler, thiophene and ferric chloride described in step A3 is 20:3:1:6.
[0012] Further, the modified filler is prepared by the following steps:
[0013] Step B1: Mix carbon nanotubes, sulfuric acid solution and nitric acid solution, react for 3-5 hours at a speed of 120-150 r / min and a temperature of 90-100° C. to obtain carboxylated carbon nanotubes; mix carboxylated carbon nanotubes, diethanolamine, dicyclohexylcarbodiimide and DMF, react for 3-5 hours at a speed of 120-150 r / min and a temperature of 40-50° C.; add epichlorohydrin and boron trifluoride etherate, heat to 65-70° C., react for 2-3 hours; add sodium hydroxide solution, react for 3-5 hours to obtain pretreated carbon nanotubes;
[0014] Step B2: The pretreated carbon tube, 2-aminoterephthalic acid and DMF are mixed evenly, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min, a temperature of 40-50°C, and a pH value of 10-11, and the pH value is adjusted to be acidic to obtain a modified carbon tube. The modified carbon tube, terephthalic acid, copper acetate, DMF and deionized water are mixed evenly, and the reaction is carried out for 10-15 hours at a speed of 60-80 r / min and a temperature of 40-50°C to obtain a precursor;
[0015] Step B3: The precursor, trifluoroacetic acid, p-toluenesulfonic acid and toluene are mixed evenly, reacted at a speed of 120-150 r / min and a temperature of 110-120°C for 8-10 hours, filtered to remove the filtrate, and the substrate is dispersed in tetrahydrofuran. At a speed of 60-80 r / min and a temperature of 0°C, thiophene-3-acetic acid and triethylamine are added with stirring, the temperature is raised to 20-25°C, and the reaction is carried out for 2-3 hours to obtain a modified filler.
[0016] Furthermore, the amount ratio of the carbon nanotubes, sulfuric acid solution and nitric acid solution described in step B1 is 0.5g:6mL:2mL, the mass fraction of the sulfuric acid solution is 95%, the mass fraction of the nitric acid solution is 65%, the amount ratio of the carboxyl groups on the carboxylated carbon nanotubes, diethanolamine, dicyclohexylcarbodiimide, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution is 10mmo l:10mmo l:12mmo l:20mmo l:0.3g:20mL, and the mass fraction of the sodium hydroxide solution is 25%.
[0017] Furthermore, the molar ratio of the epoxy group on the pretreated carbon tube in step B2 to 2-aminoterephthalic acid is 1:1, and the amount ratio of the modified carbon tube, terephthalic acid, copper acetate, DMF and deionized water is 0.5g:2g:2g:10mL:20mL.
[0018] Furthermore, the molar ratio of the hydroxyl group on the precursor of step B3 to trifluoroacetic acid is 1:1.1, the amount of p-toluenesulfonic acid is 1% of the mass of trifluoroacetic acid, and the amount ratio of the substrate, thiophene-3-acetic acid and triethylamine is 1g:5g:20mL.
[0019] The beneficial effects of the invention are as follows: an antistatic plastic packaging film prepared by the invention uses thiophene-3-ethanol and acryloyl chloride as raw materials, so that the hydroxyl group on the thiophene-3-ethanol reacts with the acyl chloride group of the acryloyl chloride to obtain a modified monomer, methacryloyloxyethyl trimethylammonium chloride, 4-vinylaniline and the modified monomer are polymerized to obtain an additive, the additive is reacted with maleic anhydride, so that the amino group on the side chain of the additive and the maleic anhydride undergo a ring-opening reaction and then a ring-closing reaction to form a maleimide structure to obtain a modified additive, the modified additive is grafted with high-density polyethylene to obtain functionalized polyethylene, the functionalized polyethylene, the modified filler and thiophene are reacted under the action of ferric chloride to form polythiophene between the functionalized polyethylene molecules and the modified filler to obtain the modified polyethylene, and the modified polyethylene is extruded and blown into a film to obtain the antistatic plastic packaging film.
[0020] The modified filler is treated with sulfuric acid and nitric acid with carbon nanotubes as raw materials to make carboxyl groups grafted on the surface to obtain carboxylated carbon nanotubes, the carboxylated carbon nanotubes are reacted with ethylene glycol amine to make the carboxyl groups on the carboxylated carbon nanotubes react with the primary amines on the ethylene glycol amine to undergo a dehydration reaction, the carbon nanotubes are reacted with epichlorohydrin to make the epoxy groups on the epichlorohydrin react with the hydroxyl groups, and finally a new epoxy group is formed by ring closure under the action of a sodium hydroxide solution to obtain a pretreated carbon tube, the pretreated carbon tube is reacted with 2-aminoterephthalic acid to make the epoxy groups on the pretreated carbon tube react with the amino groups on the 2-aminoterephthalic acid to obtain a modified carbon tube, the modified carbon tube, terephthalic acid and copper acetate are reacted to form a copper organic framework on the surface of the modified carbon tube to obtain a precursor, the precursor is esterified with trifluoroacetic acid to make the hydroxyl groups on the surface of the precursor react with the carboxyl groups on the trifluoroacetic acid, and the precursor is exchanged with thiophene-3-acetic acid to obtain a modified filler.
[0021] The antistatic plastic packaging film has a good conductive effect. The side chain of the modified polyethylene molecule contains a quaternary ammonium salt structure. The quaternary ammonium salt can absorb water in the air on the surface of the packaging film to form a continuous conductive film. At the same time, a polythiophene structure is contained between the functionalized polyethylene molecule and the modified filler. The polythiophene structure contains a π bridge structure, which can absorb electrons and conduct electrons. Together with the modified filler, a conductive channel is formed inside the packaging film, and then a conductive grid is formed, which greatly improves the antistatic performance. The antistatic effect of the packaging film will not disappear due to long-term use, and the service life of the packaging film is increased. The modified filler increases the mechanical properties of the packaging film and prevents the film from being damaged during transportation. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] A method for preparing an antistatic plastic packaging film specifically comprises the following steps:
[0025] Step A1: Thiophene-3-ethanol, acryloyl chloride, triethylamine and tetrahydrofuran are mixed, and reacted at a speed of 120 r / min and a temperature of 45° C. for 10 hours to obtain a modified monomer; methacryloyloxyethyl trimethylammonium chloride, 4-vinylaniline, the modified monomer and DMF are evenly mixed, and stirred at a speed of 200 r / min and a temperature of 75° C., and azobisisobutyronitrile is added, and the mixture is reacted for 5 hours to obtain an additive;
[0026] Step A2: The additive, maleic anhydride, toluene and DMF are mixed, and the reaction is carried out at a speed of 120 r / min and a temperature of 20° C. for 1 hour, and then p-toluenesulfonic acid is added, and the temperature is raised to 110° C. and the reaction is continued for 3 hours to obtain a modified additive. The modified additive, high-density polyethylene, dibenzoyl peroxide and toluene are evenly mixed, and the reaction is carried out at a temperature of 150° C. for 4 hours to obtain a functionalized polyethylene;
[0027] Step A3: Evenly mix the functionalized polyethylene, modified filler, thiophene and toluene, stir and add ferric chloride at a speed of 60 r / min and a temperature of 100°C, react for 10 hours, remove the ferric chloride to obtain modified polyethylene, add the modified polyethylene into a twin-screw extruder, extrude and blow mold into a film at a temperature range of 160°C, 170°C, 170°C, 175°C, 185°C, 175°C and 170°C to obtain an antistatic plastic packaging film.
[0028] The molar ratio of thiophene-3-ethanol, acryloyl chloride and triethylamine described in step A1 is 1:1:1.1, the molar ratio of methacryloyloxyethyltrimethylammonium chloride, 4-vinylaniline and modified monomer is 4:1:2, and the amount of azobisisobutyronitrile is 0.3% of the total mass of methacryloyloxyethyltrimethylammonium chloride, 4-vinylaniline and modified monomer.
[0029] The molar ratio of the amino group and maleic anhydride on the additive described in step A2 is 1:1.1, the amount of p-toluenesulfonic acid is 30% of the mass of the additive and maleic anhydride, the amount ratio of the modified additive, high-density polyethylene, dibenzoyl peroxide and toluene is 0.5g:5g:0.25g:40mL, and the high-density polyethylene model is M80064.
[0030] The mass ratio of the functionalized polyethylene, modified filler, thiophene and ferric chloride described in step A3 is 20:3:1:6.
[0031] The modified filler is prepared by the following steps:
[0032] Step B1: Mix carbon nanotubes, sulfuric acid solution and nitric acid solution, react for 3 hours at a speed of 120 r / min and a temperature of 90°C to obtain carboxylated carbon nanotubes; mix carboxylated carbon nanotubes, diethanolamine, dicyclohexylcarbodiimide and DMF, react for 3 hours at a speed of 120 r / min and a temperature of 40°C, add epichlorohydrin and boron trifluoride ether, heat to 65°C, react for 2 hours, add sodium hydroxide solution, and react for 3 hours to obtain pretreated carbon nanotubes;
[0033] Step B2: The pretreated carbon tube, 2-aminoterephthalic acid and DMF were mixed evenly, and the reaction was carried out for 3 hours at a speed of 120 r / min, a temperature of 40°C and a pH value of 10, and the pH value was adjusted to be acidic to obtain a modified carbon tube. The modified carbon tube, terephthalic acid, copper acetate, DMF and deionized water were mixed evenly, and the reaction was carried out for 10 hours at a speed of 60 r / min and a temperature of 40°C to obtain a precursor;
[0034] Step B3: The precursor, trifluoroacetic acid, p-toluenesulfonic acid and toluene are mixed evenly, reacted at a speed of 120 r / min and a temperature of 110°C for 8 hours, and then the filtrate is filtered to remove the filtrate. The substrate is dispersed in tetrahydrofuran, stirred at a speed of 60 r / min and a temperature of 0°C, thiophene-3-acetic acid and triethylamine are added, the temperature is raised to 20°C, and the reaction is carried out for 2 hours to obtain a modified filler.
[0035] The amount ratio of the carbon nanotubes, sulfuric acid solution and nitric acid solution described in step B1 is 0.5g:6mL:2mL, the mass fraction of the sulfuric acid solution is 95%, the mass fraction of the nitric acid solution is 65%, the amount ratio of the carboxyl groups on the carboxylated carbon nanotubes, diethanolamine, dicyclohexylcarbodiimide, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution is 10mmo l:10mmol:12mmo l:20mmo l:0.3g:20mL, and the mass fraction of the sodium hydroxide solution is 25%.
[0036] The molar ratio of the epoxy group on the pretreated carbon tubes and 2-aminoterephthalic acid in step B2 is 1:1, and the amount ratio of the modified carbon tubes, terephthalic acid, copper acetate, DMF and deionized water is 0.5g:2g:2g:10mL:20mL.
[0037] The molar ratio of the hydroxyl group on the precursor and trifluoroacetic acid in step B3 is 1:1.1, the amount of p-toluenesulfonic acid is 1% of the mass of trifluoroacetic acid, and the amount ratio of the substrate, thiophene-3-acetic acid and triethylamine is 1g:5g:20mL.
[0038] Example 2
[0039] A method for preparing an antistatic plastic packaging film specifically comprises the following steps:
[0040] Step A1: Thiophene-3-ethanol, acryloyl chloride, triethylamine and tetrahydrofuran are mixed, and reacted at a speed of 120 r / min and a temperature of 50° C. for 13 hours to obtain a modified monomer; methacryloyloxyethyl trimethylammonium chloride, 4-vinylaniline, the modified monomer and DMF are evenly mixed, and stirred at a speed of 200 r / min and a temperature of 78° C., and azobisisobutyronitrile is added, and the mixture is reacted for 6 hours to obtain an additive;
[0041] Step A2: The additive, maleic anhydride, toluene and DMF are mixed, and the reaction is carried out at a speed of 120 r / min and a temperature of 25° C. for 1.3 hours, and then p-toluenesulfonic acid is added, and the temperature is raised to 115° C. and the reaction is continued for 4 hours to obtain a modified additive. The modified additive, high-density polyethylene, dibenzoyl peroxide and toluene are evenly mixed, and the reaction is carried out at a temperature of 153° C. for 5 hours to obtain a functionalized polyethylene;
[0042] Step A3: Evenly mix the functionalized polyethylene, modified filler, thiophene and toluene, stir and add ferric chloride at a speed of 60 r / min and a temperature of 105°C, react for 13 hours, remove the ferric chloride to obtain modified polyethylene, add the modified polyethylene into a twin-screw extruder, extrude and blow mold into a film at a temperature range of 160°C, 170°C, 170°C, 175°C, 185°C, 175°C and 170°C to obtain an antistatic plastic packaging film.
[0043] The molar ratio of thiophene-3-ethanol, acryloyl chloride and triethylamine described in step A1 is 1:1:1.1, the molar ratio of methacryloyloxyethyltrimethylammonium chloride, 4-vinylaniline and modified monomer is 4:1:2, and the amount of azobisisobutyronitrile is 0.3% of the total mass of methacryloyloxyethyltrimethylammonium chloride, 4-vinylaniline and modified monomer.
[0044] The molar ratio of the amino group and maleic anhydride on the additive described in step A2 is 1:1.1, the amount of p-toluenesulfonic acid is 30% of the mass of the additive and maleic anhydride, the amount ratio of the modified additive, high-density polyethylene, dibenzoyl peroxide and toluene is 0.5g:5g:0.25g:40mL, and the high-density polyethylene model is M80064.
[0045] The mass ratio of the functionalized polyethylene, modified filler, thiophene and ferric chloride described in step A3 is 20:3:1:6.
[0046] The modified filler is prepared by the following steps:
[0047] Step B1: Mix carbon nanotubes, sulfuric acid solution and nitric acid solution, react for 4 hours at a speed of 120 r / min and a temperature of 95°C to obtain carboxylated carbon nanotubes; mix carboxylated carbon nanotubes, diethanolamine, dicyclohexylcarbodiimide and DMF, react for 4 hours at a speed of 120 r / min and a temperature of 45°C, add epichlorohydrin and boron trifluoride etherate, heat to 68°C, react for 2 hours, add sodium hydroxide solution, and react for 4 hours to obtain pretreated carbon nanotubes;
[0048] Step B2: The pretreated carbon tube, 2-aminoterephthalic acid and DMF were mixed evenly, and the reaction was carried out for 4 hours at a speed of 120 r / min, a temperature of 45°C and a pH value of 11, and the pH value was adjusted to be acidic to obtain a modified carbon tube. The modified carbon tube, terephthalic acid, copper acetate, DMF and deionized water were mixed evenly, and the reaction was carried out for 13 hours at a speed of 60 r / min and a temperature of 45°C to obtain a precursor;
[0049] Step B3: The precursor, trifluoroacetic acid, p-toluenesulfonic acid and toluene are mixed evenly, reacted at a speed of 120 r / min and a temperature of 115°C for 9 hours, and then the filtrate is filtered to remove the filtrate. The substrate is dispersed in tetrahydrofuran, stirred at a speed of 60 r / min and a temperature of 0°C, thiophene-3-acetic acid and triethylamine are added, the temperature is raised to 23°C, and the reaction is carried out for 2.5 hours to obtain a modified filler.
[0050] The amount ratio of the carbon nanotubes, sulfuric acid solution and nitric acid solution described in step B1 is 0.5g:6mL:2mL, the mass fraction of the sulfuric acid solution is 95%, the mass fraction of the nitric acid solution is 65%, the amount ratio of the carboxyl groups on the carboxylated carbon nanotubes, diethanolamine, dicyclohexylcarbodiimide, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution is 10mmo l:10mmol:12mmo l:20mmo l:0.3g:20mL, and the mass fraction of the sodium hydroxide solution is 25%.
[0051] The molar ratio of the epoxy group on the pretreated carbon tubes and 2-aminoterephthalic acid in step B2 is 1:1, and the amount ratio of the modified carbon tubes, terephthalic acid, copper acetate, DMF and deionized water is 0.5g:2g:2g:10mL:20mL.
[0052] The molar ratio of the hydroxyl group on the precursor and trifluoroacetic acid in step B3 is 1:1.1, the amount of p-toluenesulfonic acid is 1% of the mass of trifluoroacetic acid, and the amount ratio of the substrate, thiophene-3-acetic acid and triethylamine is 1g:5g:20mL.
[0053] Example 3
[0054] A method for preparing an antistatic plastic packaging film specifically comprises the following steps:
[0055] Step A1: Thiophene-3-ethanol, acryloyl chloride, triethylamine and tetrahydrofuran are mixed, and reacted for 15 hours at a speed of 150 r / min and a temperature of 50° C. to obtain a modified monomer; methacryloyloxyethyl trimethylammonium chloride, 4-vinylaniline, the modified monomer and DMF are evenly mixed, and azobisisobutyronitrile is added under stirring at a speed of 300 r / min and a temperature of 80° C., and the mixture is reacted for 7 hours to obtain an additive;
[0056] Step A2: The additive, maleic anhydride, toluene and DMF are mixed, and the reaction is carried out at a speed of 150 r / min and a temperature of 25° C. for 1.5 hours, and then p-toluenesulfonic acid is added, and the temperature is raised to 120° C. and the reaction is continued for 5 hours to obtain a modified additive. The modified additive, high-density polyethylene, dibenzoyl peroxide and toluene are evenly mixed, and the reaction is carried out at a temperature of 155° C. for 6 hours to obtain a functionalized polyethylene;
[0057] Step A3: Evenly mix the functionalized polyethylene, modified filler, thiophene and toluene, stir and add ferric chloride at a speed of 80 r / min and a temperature of 110°C, react for 15 hours, remove the ferric chloride to obtain modified polyethylene, add the modified polyethylene into a twin-screw extruder, extrude and blow mold into a film at a temperature range of 160°C, 170°C, 170°C, 175°C, 185°C, 175°C and 170°C to obtain an antistatic plastic packaging film.
[0058] The molar ratio of thiophene-3-ethanol, acryloyl chloride and triethylamine described in step A1 is 1:1:1.1, the molar ratio of methacryloyloxyethyltrimethylammonium chloride, 4-vinylaniline and modified monomer is 4:1:2, and the amount of azobisisobutyronitrile is 0.3% of the total mass of methacryloyloxyethyltrimethylammonium chloride, 4-vinylaniline and modified monomer.
[0059] The molar ratio of the amino group and maleic anhydride on the additive described in step A2 is 1:1.1, the amount of p-toluenesulfonic acid is 30% of the mass of the additive and maleic anhydride, the amount ratio of the modified additive, high-density polyethylene, dibenzoyl peroxide and toluene is 0.5g:5g:0.25g:40mL, and the high-density polyethylene model is M80064.
[0060] The mass ratio of the functionalized polyethylene, modified filler, thiophene and ferric chloride described in step A3 is 20:3:1:6.
[0061] The modified filler is prepared by the following steps:
[0062] Step B1: carbon nanotubes, sulfuric acid solution and nitric acid solution are mixed, and the reaction is carried out for 5 hours at a speed of 150 r / min and a temperature of 100° C. to obtain carboxylated carbon nanotubes; carboxylated carbon nanotubes, diethanolamine, dicyclohexylcarbodiimide and DMF are mixed, and the reaction is carried out for 5 hours at a speed of 150 r / min and a temperature of 50° C.; epichlorohydrin and boron trifluoride ether are added, the temperature is raised to 70° C., the reaction is carried out for 3 hours, and sodium hydroxide solution is added, and the reaction is carried out for 5 hours to obtain pretreated carbon nanotubes;
[0063] Step B2: The pretreated carbon tube, 2-aminoterephthalic acid and DMF were mixed evenly, and the reaction was carried out for 5 hours at a speed of 150 r / min, a temperature of 50°C and a pH value of 11, and the pH value was adjusted to be acidic to obtain a modified carbon tube. The modified carbon tube, terephthalic acid, copper acetate, DMF and deionized water were mixed evenly, and the reaction was carried out for 15 hours at a speed of 80 r / min and a temperature of 50°C to obtain a precursor;
[0064] Step B3: The precursor, trifluoroacetic acid, p-toluenesulfonic acid and toluene are mixed evenly, reacted at a speed of 150 r / min and a temperature of 120°C for 10 hours, and then the filtrate is filtered to remove the filtrate. The substrate is dispersed in tetrahydrofuran, stirred at a speed of 80 r / min and a temperature of 0°C, thiophene-3-acetic acid and triethylamine are added, the temperature is raised to 25°C, and the reaction is carried out for 3 hours to obtain a modified filler.
[0065] The amount ratio of the carbon nanotubes, sulfuric acid solution and nitric acid solution described in step B1 is 0.5g:6mL:2mL, the mass fraction of the sulfuric acid solution is 95%, the mass fraction of the nitric acid solution is 65%, the amount ratio of the carboxyl groups on the carboxylated carbon nanotubes, diethanolamine, dicyclohexylcarbodiimide, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution is 10mmo l:10mmol:12mmo l:20mmo l:0.3g:20mL, and the mass fraction of the sodium hydroxide solution is 25%.
[0066] The molar ratio of the epoxy group on the pretreated carbon tubes and 2-aminoterephthalic acid in step B2 is 1:1, and the amount ratio of the modified carbon tubes, terephthalic acid, copper acetate, DMF and deionized water is 0.5g:2g:2g:10mL:20mL.
[0067] The molar ratio of the hydroxyl group on the precursor and trifluoroacetic acid in step B3 is 1:1.1, the amount of p-toluenesulfonic acid is 1% of the mass of trifluoroacetic acid, and the amount ratio of the substrate, thiophene-3-acetic acid and triethylamine is 1g:5g:20mL.
[0068] Comparative Example 1: Compared with Example 1, no modified monomer was added in this comparative example, and the remaining steps were the same.
[0069] Comparative Example 2: Compared with Example 1, methacryloyloxyethyl trimethylammonium chloride was not added in this comparative example, and the remaining steps were the same.
[0070] Comparative Example 3: Compared with Example 1, this comparative example uses high-density polyethylene instead of functionalized polyethylene, and the remaining steps are the same.
[0071] Comparative Example 4: Compared with Example 1, this comparative example uses carbon nanotubes instead of modified fillers, and the remaining steps are the same.
[0072] Comparative Example 5: Compared with Example 1, this comparative example uses a precursor instead of a modified filler, and the remaining steps are the same.
[0073] The modified polyethylene obtained in Examples 1-3 and Comparative Examples 1-5 was made into strips with a diameter of 2.5 cm and a thickness of 500 μm. According to the standard of GB / T1410-2006, the test voltage was 100 V and the test was charged for 30 seconds to detect the antistatic effect. The strips were wiped with distilled water for 1 minute and dried to detect the surface resistivity. The modified polyethylene was made into Type 5 specimens according to the standard of GB / T1040.3-2006 and the tensile properties were tested at a tensile speed of 50 mm / min. The modified polyethylene was made into a specimen of 80 mm×10 mm×4 mm. According to the standard of GB / T1843-2008, the impact properties were tested. The test results are shown in the following table.
[0074]
[0075] It can be seen from the above table that the present invention has good antistatic effect and mechanical properties.
[0076] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing an antistatic plastic packaging film, characterized in that: The specific steps include: Step A1: thiophene-3-ethanol, acryloyl chloride, triethylamine and tetrahydrofuran are mixed and reacted to obtain a modified monomer, methacryloyloxyethyl trimethylammonium chloride, 4-vinylaniline, the modified monomer and DMF are mixed and stirred, and azobisisobutyronitrile is added to react to obtain an additive; Step A2: After the additive, maleic anhydride, toluene and DMF are mixed for reaction, p-toluenesulfonic acid is added, and the temperature is raised for reaction to obtain a modified additive, and the modified additive, high-density polyethylene, dibenzoyl peroxide and toluene are mixed for reaction to obtain a functionalized polyethylene; Step A3: functionalized polyethylene, modified filler, thiophene and toluene are mixed and stirred, and ferric chloride is added, and after reaction, the ferric chloride is removed to obtain modified polyethylene, and the modified polyethylene is extruded and blown into a film to obtain an antistatic plastic packaging film; The modified filler is prepared by the following steps: Step B1: mixing carbon nanotubes, sulfuric acid solution and nitric acid solution to react to obtain carboxylated carbon nanotubes, mixing carboxylated carbon nanotubes, diethanolamine, dicyclohexylcarbodiimide and DMF to react, adding epichlorohydrin and boron trifluoride etherate, heating to react, adding sodium hydroxide solution to react, and obtaining pretreated carbon nanotubes; Step B2: pre-treated carbon tubes, 2-aminoterephthalic acid and DMF are mixed and reacted, and the pH value is adjusted to be acidic to obtain modified carbon tubes; modified carbon tubes, terephthalic acid, copper acetate, DMF and deionized water are mixed and reacted to obtain a precursor; Step B3: After the precursor, trifluoroacetic acid, p-toluenesulfonic acid and toluene are mixed and reacted, the filtrate is removed by filtration, the substrate is dispersed in tetrahydrofuran, thiophene-3-acetic acid and triethylamine are added while stirring, and the temperature is raised to react to obtain a modified filler.
2. The method for preparing an antistatic plastic packaging film according to claim 1, characterized in that: The molar ratio of thiophene-3-ethanol, acryloyl chloride and triethylamine in step A1 is 1:1:1.1, and the molar ratio of methacryloyloxyethyltrimethylammonium chloride, 4-vinylaniline and modified monomer is 4:1:
2.
3. The method for preparing an antistatic plastic packaging film according to claim 1, characterized in that: The molar ratio of the amino group and maleic anhydride on the additive in step A2 is 1:1.1, and the usage ratio of the modified additive, high-density polyethylene, dibenzoyl peroxide and toluene is 0.5g:5g:0.25g:40mL.
4. The method for preparing an antistatic plastic packaging film according to claim 1, characterized in that: The mass ratio of the functionalized polyethylene, modified filler, thiophene and ferric chloride described in step A3 is 20:3:1:
6.
5. The method for preparing an antistatic plastic packaging film according to claim 1, characterized in that: The amount ratio of the carbon nanotubes, sulfuric acid solution and nitric acid solution described in step B1 is 0.5g:6mL:2mL, and the amount ratio of the carboxyl groups on the carboxylated carbon nanotubes, diethanolamine, dicyclohexylcarbodiimide, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution is 10mmol:10mmol:12mmol:20mmol:0.3g:20mL.
6. The method for preparing an antistatic plastic packaging film according to claim 1, characterized in that: The molar ratio of the epoxy group on the pretreated carbon tubes and 2-aminoterephthalic acid in step B2 is 1:1, and the amount ratio of the modified carbon tubes, terephthalic acid, copper acetate, DMF and deionized water is 0.5g:2g:2g:10mL:20mL.
7. The method for preparing an antistatic plastic packaging film according to claim 1, characterized in that: The molar ratio of the hydroxyl group on the precursor and trifluoroacetic acid in step B3 is 1:1.1, and the amount ratio of the substrate, thiophene-3-acetic acid and triethylamine is 1 g:5 g:20 mL.
8. An antistatic plastic packaging film, characterized in that: Prepared according to any one of claims 1 to 7.
Citation Information
Patent Citations
Polyolefin plastic pipeline and preparation method thereof
CN116285085A
Oxygen-resistant, antibacterial and heat-resistant polyethylene pipe and preparation method thereof
CN117186320A